Role of agroforestry in human livelihoods and biodiversity management - Arunachalam, K.; Arunachalam, A. (Indian Journal of Agroforestry, 2020)
Trees outside forests play a vital role in adding to the existing pool of biological diversity and also the carbon stock. In this regard, the trees in agro-ecosystems have much more significance owing to the various tangible and intangible benefits as appropriately understood in the agroforestry systems. Agroforestry has been the traditional practice of several indigenous communities and therefore has tremendous socio-economic bearing. Thus, agroforestry or farm forestry in the Country can be an important tool for balancing biodiversity conservation with climate resilience.